2023
DOI: 10.1186/s42836-023-00164-9
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use disorder is associated with shorter length of stay and increased home discharge after primary total joint arthroplasty: a propensity-weighted analysis

Abstract: Introduction Increased legalization of cannabis use across the United States has been correlated with increased cannabis use in the clinical setting. However, little is known regarding the characteristics and postoperative outcomes after primary joint arthroplasty (TJA) for patients with cannabis use disorder (CUD). Methods This retrospective cohort study used data from the National Inpatient Sample of patients undergoing primary TJA between 2006 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…CUD was associated with a lower likelihood of an extended length of stay, as well as an increased chance to be discharged home or leave against medical advice. While the reasons for these findings are multifactorial, patients dependent on cannabis use may be incentivized to leave the hospital sooner and return home to resume cannabis and other substance use 54 . While the current study did not examine readmission or postdischarge complications, other data have suggested the CUD may lead to postoperative, postdischarge health risks due to behavioral changes and reduced engagement in social or occupational activities 54 .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…CUD was associated with a lower likelihood of an extended length of stay, as well as an increased chance to be discharged home or leave against medical advice. While the reasons for these findings are multifactorial, patients dependent on cannabis use may be incentivized to leave the hospital sooner and return home to resume cannabis and other substance use 54 . While the current study did not examine readmission or postdischarge complications, other data have suggested the CUD may lead to postoperative, postdischarge health risks due to behavioral changes and reduced engagement in social or occupational activities 54 .…”
Section: Discussionmentioning
confidence: 71%
“…54 While the current study did not examine readmission or postdischarge complications, other data have suggested the CUD may lead to postoperative, postdischarge health risks due to behavioral changes and reduced engagement in social or occupational activities. 54 In turn, while data from the current study demonstrated no association with in-hospital risk of morbidity or mortality, future studies need to assess long-term outcomes and general health of cancer patients relative to long-term cannabis use. Surgeons and healthcare teams should be mindful of discussing the usage of cannabis with patients, understanding that these discussions can often be complex due to social, cultural, and regulatory factors.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…11,21 This effect has been associated with an elevated risk of perioperative cardiovascular complications 5 and VTE in trauma 22 and orthopaedic patients. 23 Among plastic and reconstructive surgeons, DVT remains a concerning complication. Breast reconstruction patients face an elevated baseline risk of VTE due to underlying malignancy, prolonged procedure times, and the necessity for postoperative hospitalization, with incidence reported between 0.13 and 6% amongst various studies.…”
Section: Discussionmentioning
confidence: 99%